The Impact of Deregulation and Financial Innovation on Consumers: The Case of the Mortgage Market - GERARDI, KRISTOPHER S.; ROSEN, HARVEY S.; WILLEN, PAUL S. (Journal of Finance, 2010)
ABSTRACT We develop a technique to assess the impact of changes in mortgage markets on households, exploiting an implication of the permanent income hypothesis: The higher a household's expected future income, the higher its desired consumption, ceteris paribus. With perfect credit markets, desired consumption matches actual consumption and current spending forecasts future income. Because credit market imperfections mute this effect, the extent to which house spending predicts future income measures the “imperfectness” of mortgage markets. Using micro‐data, we find that since the early 1980s, mortgage markets have become less imperfect in this sense, and securitization has played an important role.